CXCL5 into the upper airways of children with influenza A virus infection - Duemmler, Annett; Montes-Vizuet, Aurea Rosalía; Santiago Cruz, Julio; Manuel Terán, Luis (Revista Médica del Instituto Mexicano del Seguro Social, 2021)
Background: neutrophil infiltration is a major feature in the pathogenesis of influenza infection. The factors regulating the neutrophil influx are not fully understood. The chemokine CXCL5/ENA-78 is a potent neutrophil chemoattractant, that has been implicated in several inflammatory diseases. Our objectives was to study the release of CXCL5 in children with natural acquired influenza.Methods: CXCL5 concentration was investigated by immunoenzyme assay in nasal aspirates of children (n = 18) in whom respiratory symptoms were precipitated predominantly by influenza A virus.Results: there were increased CXCL5 levels in nasal aspirates when children were symptomatic as compared with samples from the same children when they had been asymptomatic for four weeks (medians 1850 pg/mL vs. 30 pg/mL, p < 0.005). We purified CXCL5 from these samples, and demonstrated biological neutrophil chemotactic activity.Conclusions: it is the first in vivo data that suggest an important role for CXCL5 in neutrophil influx in proven upper respiratory influenza infection. We suggest that CXCL5 might provide a target for therapeutic intervention in influenza induced respiratory diseases.